Front-End and Back-End Impedance Calculation in Terms of ABCD Parameters of a Two-Port Network and Broadband Impedance Matching - ŞENGÜL, METİN (Emerald Publishing, 2025)
PurposeBroadband impedance matching is a well-studied subject in the literature, where the matching network is typically derived after optimizing the transducer power gain (TPG). The crux of broadband impedance matching is to calculate the front-end or back-end impedance values for use in the TPG expression. The purpose of this study is to determine the front-end or back-end impedance values in a straightforward manner in terms of transmission (ABCD) parameters of the matching network, load impedance or generator impedance values, respectively, and to generate initial component values for computer-aided design (CAD) tools to optimize the power transfer capability of the matching network.Design/methodology/approachThe proposed method begins by supplying the designer defined scattering parameters. The remaining parameters are then calculated under constraints ensuring a realizable network. The ABCD parameters are derived from the scattering parameters, and the front-end or back-end impedance values are computed. Finally, TPG optimization is performed to maximize power transfer and component values are obtained via the front-end or back-end impedances or corresponding reflections.FindingsThe proposed front-end or back-end impedance calculation approach is applied to broadband impedance matching examples, demonstrating that the performance of the designed matching networks closely matches those obtained using established techniques in the literature. The performance of the matching network designed using the proposed approach can be further improved via CAD tools.Originality/valueThe key advantages of this approach are: only a single optimization step is required; the calculation of front-end or back-end impedances is simplified; computational complexity is significantly reduced; applicable to both double-matching (complex generator and load impedances) and single-matching (complex load impedance, real generator impedance) problems.
Keywords: Circuits; Equalizers; Impedance Matching; Passive Networks; Transducer Power Gain